Application Value of Music Therapy in Improving the Emotional State and Quality of Life of Hospitalized Patients with Breast Cancer: Retrospective Study - Juan Guo; Zhongzhen Yu; Xinping Xiao; Jie Dong (Noise and Health)
Objective: This study aimed to apply music therapy as a clinical treatment for patients with breast cancer (BC) experiencing mild or moderate depression during hospitalization and observe any improvements in their depression and quality of life. Methods: A total of 102 patients who had mild-to-moderate depression, were diagnosed with BC, and were admitted to our hospital from October 2022 to October 2023 were selected as the subjects of a retrospective analysis. According to their participation in short-term music therapy, they were divided into a control group (routine nursing treatment n = 45) and an observation group (routine nursing treatment + music therapy n = 57). Self-rating depression (SDS) scale and functional assessment of cancer therapy-breast (FACT-B) scale Chinese version 4.0 scores and patient satisfaction after treatment were compared between the two groups. Results: After treatment, the SDS scale scores and FACT-B scores of the observation group were significantly better than those of the control group (P < 0.001). The patient satisfaction in the observation group was higher than in the control group (P < 0.05). Conclusion: Music therapy is a highly safe method to improve the depression and quality of life of patients with BC. It also provides a simple and convenient nondrug clinical treatment with broad application prospects.